2021
DOI: 10.17159/2310-3833/2021/vol51n1a8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substance Use Disorder on Women's Roles and Occupational Participation

Abstract: Introduction: Literature regarding the psychosocial sequelae of substance abuse is largely androcentric and limited regarding the negative effects on women's functioning. This study aims to explore the effects of substance abuse on the roles and occupations of women. Methods: This phenomenological qualitative study utilized a purposive snowball sampling strategy to recruit women with a history of substance abuse. Semi-structured interviews were conducted with six participants. Findings: Six main themes emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The initial two and final sessions focused on education and planning, familiarizing participants with leisure concepts, identifying barriers and facilitators to leisure, understanding preferred and available leisure activities, and developing personalized leisure plans. The remaining sessions [3][4][5][6][7][8][9][10][11] involved practical activities where the group engaged in chosen leisure occupations together. A comprehensive list of leisure occupations was initially compiled based on a literature review, considering evidence and documentation in the field of leisure occupations.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial two and final sessions focused on education and planning, familiarizing participants with leisure concepts, identifying barriers and facilitators to leisure, understanding preferred and available leisure activities, and developing personalized leisure plans. The remaining sessions [3][4][5][6][7][8][9][10][11] involved practical activities where the group engaged in chosen leisure occupations together. A comprehensive list of leisure occupations was initially compiled based on a literature review, considering evidence and documentation in the field of leisure occupations.…”
Section: Interventionmentioning
confidence: 99%
“…Given the evidence that individuals with substance use disorder face reduced occupational participation, therapeutic interventions that emphasize the use of occupation as a means of service delivery are necessary. Among various occupations, leisure can be regarded as a key area for interventions during periods of abstinence, as leisure time is often diminished and undergoes changes in meaning and execution among most individuals with substance use disorder [ 8 ]. Leisure occupations significantly impact individuals' lives and are defined as nonmandatory activities pursued with internal motivation during free time, distinct from work, self-care, or sleep [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that occupational roles determine one's lifestyle, narrowed research regarding the effects of AUD on a woman's career is relevant for analysis. A set of researchers studying AUD and occupational participation found that alcohol abuse affects a woman's ability to engage in normal occupational activities, namely socializing and maintaining responsibilities (Rawat et al, 2021). Bush and Lipari (2016) further link specific industries to AUD, finding that those involved in "accommodations and food services," "construction," and "arts" displayed the highest rates of past year substance abuse.…”
Section: Aud and The Female Creativementioning
confidence: 99%
“…female alcoholics and the correlation between gender roles and the manifestation of AUD, offering broad information on the topic of discussion (Mulia & Bensley, 2020;Oprea et al, 2022). The small number of studies that offer a more focused view of both female and male alcoholics, such as through the lens of employment as a creative, often fail to account for the disparities experienced solely by women in specific creative professions (Rawat et al, 2021;Thomas & Duke, 2007). Moreover, specific creative professions, namely authorship, and the alcoholic have been briefly and unsystematically analyzed through the writings of male alcoholics, leaving an absence of literature surrounding a systematic analysis of the effect of AUD on a female alcoholic's writings (Djos, 1995).…”
Section: Introductionmentioning
confidence: 99%